ASPEK YURIDIS KEPEMILIKAN SAHAM BAGI KARYAWAN PADA PERSEROAN TERBUKA (PT. Tbk) - ANDREW J TARIGAN; BISMAR NASUTION; WINDHA WINDHA (TRANSPARENCY, 2013)
As part of the world community business management company in Indonesia is affected from management practices in other country,especially in advanced countries. One of the practice is introduction a manajemen program human resources the Employee Stock Ownership in a Public Company. This research is meant to see how the regulations of the employee stock ownership,how the medium and subject matter in employee stock ownership and procedure, and stock ownership in other county and indonesia. The Research Methods in this study is a yuridis empiris research that is a researching  how the Bapepam regulated and a Prior to  the Law 40 of 2007 concerning incorporated company in assessing the effect of granting shares to employees againts incorporated company. In this research, it can be seen in Indonesia no special provision how to regulate Stock Ownership Plans. The legal basis of the stock ownership plans in Indonesia be regulated in prior to the law No.40 of 2007 concerning incorporated company in clause 43 concerning about stock ownership plans, and clause 51,52 and 61 concerning about shareholder rights and organize about legal acts the company, and the legal basis of the stock ownership plans is Bapepam No.IX.D4 concerning HMETD.     Key Words: Tenaga Kerja, Kepemilikan Saham, Perusahaan Terbuka